Thermal stress analysis of butt welded joint / Karthikeyan Balasubramaniam - Karthikeyan, Balasubramaniam (2013)
In industries’ welding plays a vital role in joining process. Many of the structures presently built in space rockets, deep diving submarines and very heavy containment vessels for nuclear reactors could not have been constructed without the proper application of welding technology. It is well known fact that during welding the metal at the welding zone gets melted and then solidifies, which results in shrinkage in all the directions. Residual strain and stress distributions coming from shrinking are largely influenced by the nature and configuration of the welding process, metallurgical characteristics of weld and the geometrical shape of the weld joint. The material characteristic mainly depends on the thermal history cycle through which the specimen goes through in the process. So these thermal history cycles are to be known in order to get a better knowledge of the welding phenomenon and to minimize the risk of failures. This work describes the detail finite element procedure for determination of heat flow pattern and stress distribution on cylinder modeled with stainless steel and aluminum during welding. In this, Modified Double Ellipsoidal Distribution Pattern was modeled and considered for the weld pool design. Elasto-plastic material properties at various temperatures were also considered for simulation. A variable welding speed was used during welding and effect of the nonlinear welding speed was also studied. Transient thermal histories at various points were determined and compared with available published data. The cooling curve could be obtained from the descending region of the Transient thermal histories curve at various locations. By this metallurgical characteristic of the material at the weld zone and heat affected zone can be obtained during welding simulation process. The problems of distortion and stress distribution were also carried out. A customized programming was developed to for the welding simulation.